Body size‐dependent effects on the distribution patterns of phoretic mite species assemblages on Rhynchophorus ferrugineus (Olivier, 1790) - Inês Matos; Diogo Silva; João Oliveira; Claúdia Gonçalves; Rita Alves; Nuno Pereira; Francisco Catarino; Olga M. C. C. Ameixa; José Américo Sousa; Luis Filipe Rangel; Maria João Santos; Camilo Ayra‐Pardo (Ecology and Evolution)
Abstract Phoretic mites attach to different body parts of the red palm weevil (RPW), Rhynchophorus ferrugineus (Olivier, 1790), to disperse. However, the question of how the patterns of attachment sites are formed remains intriguing. Here, we examined RPW‐associated phoretic mites in four districts in Northern Portugal (macrohabitat), and investigated the patterns of mite distribution on six body parts of RPW (microhabitat). At the macrohabitat level, we detected seven phoretic mite taxa using the RPW host in each of the four studied districts, all documented for the first time in association with this invasive exotic species in Portugal. However, their relative abundance (species evenness) varied between districts, as did species diversity. All examined weevils carried mites, and the prevalence of the different taxa did not differ between districts or sex of weevils. Measured by mean abundance and degree of aggregation, Centrouropoda sp. proved to be the dominant taxon, while Acarus sp. and Curculanoetus rhynchophorus were considered common subordinate taxa and Uroovobella sp., Mesostigmata, Nenteria extremica and Dendrolaelaps sp. sparse taxa. At the microhabitat level, all taxa were present on all body parts of the RPW; the highest abundance was in a region encompassing the inner surface of the elytra and the membranous hind wings (subelytral space). Analysis of niche overlap revealed that the distribution patterns of phoretic mite taxa on the RPW were not randomly structured. In the subelytral space, interspecific coexistence of mites increased as a function of body size difference with the dominant Centrouropoda sp. We found that in the subelytral space the large dominant species Centrouropoda sp. displaced the larger species Uroobovella sp. and the similarly sized species Nenteria extremica, but coexisted with smaller taxa.